Competing to Commit: Markets with Rational Inattention - Cusumano, Carlo M.; Fabbri, Francesco; Pieroth, Ferdinand (American Economic Review, 2024)
Two homogeneous-good firms compete for a consumer’s unitary demand. The consumer is rationally inattentive and pays entropy costs to process information about firms’ offers. Compared to a collusion benchmark, competition produces two effects. As in standard models, competition puts downward pressure on prices. But, additionally, an attention effect arises: the consumer engages in trade more often. This alleviates the commitment problem that firms have when facing inattentive consumers and increases trade efficiency. For high enough attention costs, the attention effect dominates the effect on prices: firms’ profits are higher under competition than under collusion. (JEL D11, D21, D43, D83, L12)